Comprehensive meta-analysis of QTL and gene expression studies identify candidate genes associated with Aspergillus flavus resistance in maize - Baisakh, Niranjan; Da Silva, Eduardo A.; Pradhan, Anjan K.; Rajasekaran, Kanniah (Frontiers in Plant Science, 2023)
Aflatoxin (AF) contamination, caused by Aspergillus flavus, compromises food safety and marketability of commodities, such as maize, cotton, peanut, and tree nuts. Multigenic inheritance of AF resistance impedes conventional introgression of resistance traits into high-yielding commercial maize varieties. Several AF resistance-associated QTLs and markers are reported from multiple biparental and genome-wide association mapping studies in maize. But QTLs with large confidence intervals (CI) explaining inconsistent phenotypic variance limit their use in marker-assisted selection. Meta analysis of published QTLs can identify significant meta-QTLs (MQTLs) with narrower CI for reliable identification of genes and linked markers for AF resistance. Using 276 out of 356 reported QTLs controlling resistance to A. flavus infection and AF contamination in maize, we identified 58 MQTLs on all 10 chromosomes with a 66.5% reduction in average CI. Similarly, meta-analysis of maize genes differentially expressed in response to (a)biotic stresses from to-date published literature identified 591 genes putatively responding to only A. flavus infection, of which 14 were significantly differentially expressed (-1.0≤ Log2Fc ≥1.0; P≤0.05) only under A. flavus infection. Eight MQTLs were validated by their colocalization with 14 A. flavus resistance-associated SNPs identified from GWAS in maize. Fifteen genes were physically close between the MQTL intervals and SNPs. Assessment of 12 MQTLs-linked SSR markers identified three markers that could discriminate 14 and eight cultivars with resistant and susceptible response, respectively. Comprehensive meta-analysis of QTLs and differentially expressed genes could lead to identification of genes and makers for their potential application in marker-assisted breeding of A. flavus resistant maize varieties.